PENINGKATAN KETERAMPILAN MENYIMAK CERITA RAKYAT MENGGUNAKAN MEDIA AUDIO DI KELAS V SDN 30 PONTIANAK SELATAN - Gonsaga, Kristianus; Kaswari, Kaswari; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Â AbstractThis study to improve the skills of listening to folklore by using the audio media of students of class V State Elementary School 30 South Pontianak. The method used is descriptive method with class action research form. This study was conducted in two cycle and each cycle consisted of one meeting with time allocation of 3 x 35 minutes. Results from the teachers ability to plan lessons from cycle I with an average score 3,62 to 3,87 in cycle II. The results of the teachers ability in carrying out learning from cycle I average value 3,51 to 3,69 in cycle II. Improving skills to listen to folklore using class V audio media is evidenced by the average acquisition of students in the first cycle 76,85 and in cycle II to 88,02. So, it can be concluded that the audio media can be used to improve the skills of listening to folklore of class V State Elementary School 30 South Pontianak.Â Keywords: Listening skill, folklore, audio media